The Oracle Year - Soule, Charles (New York : Harper Perennial, 2018)
Awakening from a dream with more than one hundred predictions about the future in his head, an unassuming Manhattan bassist becomes one of the worlds most powerful men and hides his identity behind an online persona that is targeted by greedy corporations and dangerous enemies.
Keywords: Prophecies -- Fiction; Oracles -- Fiction; Cyber intelligence (Computer security) -- Fiction; Manhattan (New York, N.Y.) -- Fiction; Action and adventure fiction; Thrillers (Fiction)